Chemical-Thermal Activation to Improve the Characterization of Sludge-Based Activated Carbon (SBAC) from Palm Oil Mill Sludge (POMS) - Inema, Dinda Dwiana; Handajani, Marisa (Politeknik Negeri Malang, 2024)
The development of time and technology triggers significant challenges in preserving the environment. Large-scale industry that uses a large quantity of energy and clean water is the main reason environmental management due to industrial activities needs to be considered properly. In addition to liquid wastewater, waste in the form of sludge used in wastewater management is also a new problem that requires special attention. Sludge-based activated carbon (SBAC) is one of the options for utilizing WWTP sludge in low-cost adsorbent materials. The development of SBAC is a promising solution to solving two-way environmental problems. The most used activation method combines thermal and chemical compound impregnation. This paper aims to prove that Palm Oil Mill Sludge (POMS) can be applied as an adsorbent after chemical and thermal activation. KOH 4M was used with a ratio of 1:1 (weight/volume) with pyrolysis heating at 700oC injected with nitrogen gas (N2). Fourier Transform Infrared Spectroscopy (FTIR) test shows SBAC has hydroxyl and carboxyl functional groups, Pore Size Analyzer (PSA) classified SBAC as microporous with 1.7 nm size of SBAC, iodine number is about 821 mg/g, 23.63% of ash content, 62.96% of fixed carbon, 11.5% of water content, and 15.37% of volatile content.